European Court of Justice Secures Fundamental Rights from UN Security Council Resolutions - Sebastian Recker (Göttingen Journal of International Law)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-fareast-language:KO;} p.MsoFootnoteText, li.MsoFootnoteText, div.MsoFootnoteText {mso-style-noshow:yes; margin-top:0cm; margin-right:0cm; margin-bottom:0cm; margin-left:21.25pt; margin-bottom:.0001pt; text-align:justify; text-indent:-21.25pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-fareast-language:KO;} span.MsoFootnoteReference {mso-style-noshow:yes; vertical-align:super;} p.ArticleText, li.ArticleText, div.ArticleText {mso-style-name:"Article Text"; mso-style-update:auto; margin:0cm; margin-bottom:.0001pt; text-align:justify; text-indent:1.0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-fareast-language:KO;} /* Page Definitions */ @page {mso-footnote-separator:url("file:///C:/DOKUME~1/mlippold/LOKALE~1/Temp/msohtml1/01/clip_header.htm") fs; mso-footnote-continuation-separator:url("file:///C:/DOKUME~1/mlippold/LOKALE~1/Temp/msohtml1/01/clip_header.htm") fcs; mso-endnote-separator:url("file:///C:/DOKUME~1/mlippold/LOKALE~1/Temp/msohtml1/01/clip_header.htm") es; mso-endnote-continuation-separator:url("file:///C:/DOKUME~1/mlippold/LOKALE~1/Temp/msohtml1/01/clip_header.htm") ecs;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 70.85pt 2.0cm 70.85pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> The European Court of Justice has annulled Council Regulation (EC) No 881/2002<!--[if !supportFootnotes]-->[1]<!--[endif]--> freezing funds of Mr. Kadi and Al Barakaat based on Resolution 1267 (1999)<!--[if !supportFootnotes]-->[2]<!--[endif]--> of the United Nations Security Council<!--[if !supportFootnotes]-->[3]<!--[endif]-->. In so doing, the European Court of Justice has set aside the Court of First Instance’s judgment<!--[if !supportFootnotes]-->[4]<!--[endif]-->. The Court of First Instance held that in principle it had no jurisdiction to review the lawfulness of regulations based on Security Council resolutions. The European Court of Justice stated that acts of the Sanctions Committee under Chapter VII of the UN Charter must be reviewable if restrictions infringe general principles of Community law<!--[if !supportFootnotes]-->[5]<!--[endif]-->. This decision creates a new balance of power in international law. Obligations from international agreements cannot prejudice fundamental rights as general principles of the EC Treaty. Until this judgment, it seemed that the UN Security Council had the unconfined power to determine binding instructions to States under Chapter VII of the UN Charter without the possibility of judicial review by Member States. The conflict between the status quo demanded by the United Nations and the requirement of the European Communities in securing their general principles shows the purpose and at the same time abashment of international law. Who determines the rules in international law and who is to decide when the rules have been violated? This question is contentious, because the standing of rules in international law is dependent on the consent of the parties. In this regard, European Union Member States, institutions, citizens and courts were not agreed on how to balance the competence in these cases<!--[if !supportFootnotes]-->[6]<!--[endif]-->. For example, the Court of First Instance restricted the supervision of Security Council resolutions to jus cogens<!--[if !supportFootnotes]-->[7]<!--[endif]-->. Conversely Germany<!--[if !supportFootnotes]-->[8]<!--[endif]-->, the French Republic, the Kingdom of the Netherlands, the United Kingdom and the Council demanded exemption from all review arising from measures adopted by the Security Council under Chapter VII of the UN Charter<!--[if !supportFootnotes]-->[9]<!--[endif]-->. In contrast, the European Court of Justice and the appellants in the given cases have seen the necessity of effective judicial review if fundamental rights are infringed<!--[if !supportFootnotes]-->[10]<!--[endif]-->. However, how can international law work if there is no consent regarding the principle of supremacy? Without question this judgment has decimated the basis of tribute in international law and increased the standard of the European Communities as guardians of their general principles in international law. <!--[if !supportFootnotes]--> <!--[endif]--> <!--[if !supportFootnotes]-->[1]<!--[endif]--> Commission Regulation No. 881/2002, O.J. L 139/9 (2002). <!--[if !supportFootnotes]-->[2]<!--[endif]--> SC Res. 1267, UN SCOR, 54th sess., 4051st mtg., UN Doc. S/RES/678 (15 October 1999). <!--[if !supportFootnotes]-->[3]<!--[endif]--> Notes relating to the decision: Christoph Ohler, Gemeinschaftsrechtlicher Rechtsschutz gegen personengerichtete Sanktionen des UN Sicherheitsrates, Europäische Zeitschrift für Wirtschaftsrecht – EuZW Heft 20 (2008), 630-633;Kirsten Schmalenbach, Bedingt kooperationsbereit: Der Kontrollanspruch des EuGH bei gezielten Sanktionen der Vereinten Nationen, Juristenzeitung – JZ Heft 1 (2009), 35-43; Nikolaus Graf Vitzthum, Les compétences législatives et juridictionnelles de la Communauté européenne dans la lutte contre le terrorisme – l’affaire “Kadi”, Zeitschrift für Europarechtliche Studien – ZeuS (2008) 375-429; Michael Riegner, Bulletin of international legal developments (2008) Vol. 17, 193-196; Maja Brkan, Presekani (in spet zavezani) gordijski vozel, Pravna praksa (2008), ŠT. 36, 25-27. <!--[if !supportFootnotes]-->[4]<!--[endif]--> Ahmed Ali Yusuf and Al Barakaat International Foundation v. Council and Commission, Case T-306/01 [2005] E.C.R. II-3533, Common Market Law Review 43 (2006) 537 (‘Yusuf and Al Barakaat’); Yassin Abdullah Kadi v. Council and Commission, Case T-315/01 [2005] E.C.R. II-3649, Common Market Law Review 43 (2006) 537 (‘Kadi’). <!--[if !supportFootnotes]-->[5]<!--[endif]--> Al Barakaat International Foundation v. Council and Commission, Yassin Abdullah Kadi v. Council and Commission, Joined Cases C-402/05 P and C-415/05 P (Eur.Ct.J. 3 September 2008) (not yet reported), summarized in Weekly Proceedings of the Court of Justice 31/08, at 1 (‘Kadi and Al Barakaat’). <!--[if !supportFootnotes]-->[6]<!--[endif]--> Kadi and Al Barakaat, paras. 107-115 (ECJ). <!--[if !supportFootnotes]-->[7]<!--[endif]--> Yusuf and Al Barakaat, para. 277; Kadi, para. 226 (CFI). <!--[if !supportFootnotes]-->[8]<!--[endif]--> Frank Schorkopf, Grundgesetz und Überstaatlichkeit (2007), 152-156. <!--[if !supportFootnotes]-->[9]<!--[endif]--> Kadi and Al Barakaat, paras. 111-112, 114-115 (ECJ). <!--[if !supportFootnotes]-->[10]<!--[endif]--> Kadi and Al Barakaat, paras. 107-108, 327 (ECJ).